Respons dan Minat Masyarakat terhadap Madrasah Terakreditasi A - Mawi Khusni Albar (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2021)
Public interest in sending their children to an educational institution, one of which is determined by the quality of the educational institution. One of these qualities can be seen from the accreditation obtained. This study aims to determine the public's response to the A accreditation obtained by Madrasah Ibtidaiyah (MI) Ma'arif NU 01 Cilopadang, Majenang District, Cilacap Regency in 2018. This educational institution has received an A accreditation since 2015. The study uses a descriptive-qualitative method, and included in field research or field research. In obtaining the data, the instruments that the researcher uses are interviews, observations, and studies of related documents. The analysis is done by reducing the data, displaying the data, and drawing conclusions. In clarifying the validity of the data, the researchers carried out an extension of participation, and triangulation of sources and methods. From the research conducted, it can be seen that the level of public knowledge of the quality of accreditation of MI Ma'arif NU 1 Cilopadang is high with an average of 98.43% of respondents knowing well the quality of accreditation. The attitude of the community towards the quality of MI Ma'arif NU 1 Cilopadang Majenang accreditation is high, based on the instrument in the context of this attitude, the average result is 94.56%. the quality of accreditation has a very high significant impact where the results obtained are 89.64% of the public are interested in choosing MI Ma'arif NU 1 Cilopadang based on the results of the accreditation obtained.